Cultura maker na educação não formal: fabricação digital e arte têxtil - a integração entre tecnologias e artes - Campos, Patrícia Pereira (2023)
This research is developed in the Graduate Studies Program in Education: Curriculum, by the Pontifical Catholic University of São Paulo, in the line of Research New Technologies in Education. It aims to point out dimensions of teaching practice that allow access to and use of technologies and arts in non-formal educational contexts. The proposed research is developed in a unit of Sesc de São Paulo and seeks, through the experience of a practical activity (maker) involving the researcher and participants, to analyze digital manufacturing and textile art, using analog and digital technologies and other resources, more specifically laser cutter and more traditional weaving techniques. The theoretical foundations presented deal with Curriculum, Information and Communication Technology, Art and Communication. The approach is qualitative and experimental. Six components of teaching practice were identified that enhance access to and use of technologies and arts: curriculum; teaching practice; collaboration; hybridism; design (art and technology) and affection. Affection emerged in this research as a relevant component for collaboration and development of the construction of practice. The research concludes that in the articulation of technologies and arts, through the activity carried out, several manifestations of hybridism emerge, in addition to face-to-face and online education or the use of technologies in face-toface activities, also evidencing the complementation between formal and non-formal education